2004
DOI: 10.1111/j.1354-7798.2004.00257.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Market Segmentation and Bank Concentration on Mutual Fund Expenses and Returns: Evidence from Finland

Abstract: "A tremendous amount of research examines US mutual funds, but fund markets also thrive in other countries. However, research about these fast growing markets is lacking. This study addresses Finnish funds. Fast growth of the Finnish fund industry, strong bank dominance in the industry and recent EU membership make it an interesting market to examine. The Finnish fund market is also of particular interest since it had the fastest growth among the EU countries during 1996-2000. We find evidence that bank-manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 28 publications
3
31
2
Order By: Relevance
“…The funds that employ incentive fees have higher alpha values, which is a measure of performance, as they charge lower expenses. Furthermore, Korkeamaki and Smythe (2004) and Geranio and Zanotti (2005) with studies of smaller economies showed that fees are higher in these smaller economies, and that fees do affect returns adversely. (Babalos, Kostakis, & Philippas, 2009) evaluate the performance Greek domestic funds.…”
Section: Mutual Fund Performancementioning
confidence: 95%
“…The funds that employ incentive fees have higher alpha values, which is a measure of performance, as they charge lower expenses. Furthermore, Korkeamaki and Smythe (2004) and Geranio and Zanotti (2005) with studies of smaller economies showed that fees are higher in these smaller economies, and that fees do affect returns adversely. (Babalos, Kostakis, & Philippas, 2009) evaluate the performance Greek domestic funds.…”
Section: Mutual Fund Performancementioning
confidence: 95%
“…Although the sign is negative, the age of the fund is not reflected in a lower management cost-considered linearly, or using its natural logarithm-so that the hypothesis of the existence of a learning curve is not backed up. The lack of a learning curve is also noted in the Italian market by Geranio and Zanotti (2005) and in the Finnish market by Korkeamaki and Smythe (2004) with a surprising positive relation between both variables, age and cost. This result clashes with the empirical evidence generally observable in the North American market, which largely confirms the beneficial effect of this hypothesis.…”
Section: Management Feementioning
confidence: 83%
“…For this reason, the model is also estimated by panel data methodology. Among the studies mentioned above, this technique is only applied in Korkeamaki and Smythe (2004) and Geranio and Zanotti (2005).…”
Section: Costs Associated With Mutual Funds In Spainmentioning
confidence: 97%
See 2 more Smart Citations